(untitled) (Olhar de Professor, 2023)
The text presented is a theoretical essay originated from an integrative literary review, which aims to make considerations from the writings of Honneth and Fraser about the categories redistribution, recognition and representation as cornerstones in the production of a society that effectively shares the ideals of equality and justice announced by modernity. Epistemologically linked to the Critical Theory filosofy, the present essay highlights the importance of working with such concepts as a fundamental component in the production of an environment that denounces arbitrariness and shapes social inclusion as a possible and not just desirable event in the most varied cultural dimensions. Furthermore, it outlines how educational spaces, especially schooled, can play a central role in promoting a society configured as fair by encompassing as an organic curricular principle, from the discussion of material and identity issues that cross our existence, going to the exercise of defense the presence of all representative publics in society in democratic power arenas.